(untitled) (Nóema, 2012)
The fundamental structure of occidental metaphysics must be identified in the form of repetition of the act of negation: that’s what we try to demonstrate facing some cruxes of Aristotelian thought, since it is the main paradigm, next to the Platonic one, of the form of occidental metaphysical and scientific thinking. In this sense this research takes in turn for us a paradigmatic relation to the whole metaphysical scientific and occidental tradition.